A narrow pore size magnesium-lithium separation nanofiltration membrane and preparation method thereof
The narrow-pore magnesium lithium separation membrane prepared by anhydrous solid-liquid interface polymerization method solves the problems of low separation efficiency and uneven pore size distribution of traditional nanofiltration membranes in magnesium lithium separation, and realizes accurate separation and nanofiltration of magnesium lithium ions Improved performance, suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202211543680.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-03
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-12-03
AI Technical Summary
Traditional nanofiltration membranes have problems with low separation efficiency and uneven pore size distribution in magnesium-lithium separation, especially due to the negative charge increase and non-crosslinking sites caused by the side reaction of acid chloride hydrolysis during interfacial polymerization, which affects the magnesium-lithium Precise separation.
Using anhydrous solid-liquid interface polymerization method, the high saturation vapor pressure of amine monomers is used to produce polyamide selection with a two-dimensional network crosslinked structure by performing anhydrous reaction between amine monomers and acid chloride monomers on a porous ultrafiltration substrate. The separating layer can avoid side reactions of acid chloride hydrolysis and realize the preparation of a magnesium lithium separation membrane with narrow pore size.
The precise separation of magnesium lithium ions and the improvement of nanofiltration performance are achieved, and the separation layer grows uniformly on a variety of substrates, and is suitable for seawater desalination, salt lake lithium extraction and wastewater treatment.
Smart Images

Figure HDA0003979196400000011 
Figure HDA0003979196400000012 
Figure HDA0003979196400000013
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane separation, and in particular relates to a narrow-pore magnesium-lithium separation nanofiltration membrane and a preparation method thereof. Background Art
[0002] Lithium is a non-renewable strategic resource that is widely used in industries such as batteries, aerospace, ceramics, glass and polymer manufacturing, driving the continuous development of society. In order to solve the shortage of lithium resources in the future, ensure the reliable supply of lithium ions, and promote the sustainable development of energy, it is necessary to develop functional technology to extract lithium ions from brine with a high magnesium-to-lithium ratio.
[0003] Nanofiltration technology is a key subfield in membrane separation technology. It has the advantages of energy saving, environmental protection and ease of use. At present, nanofiltration technology has made great progress in fine separation, and it is widely used in wastewater recovery and salt water desalination. And due to the synergistic effect of molecular sieving and Donnan effect, nanofiltration technology is gradually developing into an effective and energy-saving alternative technology for extracting lithium from salt lakes. However, traditional polyamide membranes are usually negatively charged, with poor screening of monovalent and divalent cations and better separation of monovalent and divalent anions. The separation hydration radius is The magnesium ion and hydration radius are To solve this problem, we must start from the membrane manufacturing process, reduce the weight of the Donan effect caused by the negative charge on the surface of the film, and improve the uniformity of pore distribution.
[0004] The most advanced nanofiltration membranes currently in commercial use are thin film composite (TFC) membranes, which include a polyamide (PA) active layer and a porous ultrafiltration substrate, which is usually a microfiltration (MF) or ultrafiltration (UF) membrane. In terms of permeability and selectivity of TFC membranes, their nanofiltration performance is mainly determined by the PA active layer formed by interfacial polymerization (IP), and interfacial polymerization is also the most advanced method for preparing TFC membranes. In a typical IP process, amine monomers in the aqueous phase and acid chloride monomers in the organic phase diffuse to the interface separately, and once they reach the interface, they will rapidly undergo Scotten-Bauman reactions. However, in this typical interfacial polymerization process, there is without exception a side reaction, namely the hydrolysis of acyl chlorides due to the presence of water. Although this unexpected consequence increases the amount of negative charge on the membrane surface, it also causes non-crosslinking sites to appear in the fabricated polyamide nanomembrane, resulting in separation membrane defects and the well-known "trade-off" effect. Therefore, an important obstacle to magnesium-lithium separation is the development of a water-free interfacial polymerization method to prepare narrow-pore magnesium separation membranes.
[0005] On this basis, starting from the IP process, the present invention utilizes the high saturated vapor pressure of amine monomers to develop a method for anhydrous solid-liquid interfacial polymerization. This method completely eliminates the side reaction of acyl chloride hydrolysis, and the compact arrangement of amine monomers can make the polymerization reaction more intensive and orderly, thereby realizing the preparation of narrow pore separation membranes. This membrane can not only be used for efficient magnesium-lithium separation, but also has good application prospects in the field of rare earth concentration. Summary of the invention
[0006] The key technical problem to be solved by the present invention is to provide a method for preparing a narrow-pore magnesium-lithium separation nanofiltration membrane, so that the prepared separation membrane can achieve accurate separation of magnesium ions and lithium ions while ensuring good nanofiltration performance. The specific technical solution is as follows:
[0007] In a first aspect, the present invention provides a narrow pore magnesium-lithium separation nanofiltration membrane, comprising a porous ultrafiltration substrate and a polyamide selective separation layer in situ grown on the surface of the porous ultrafiltration substrate; specifically, the selective separation layer has a thickness of 2 nm to 200 nm.
[0008] The polyamide material is a two-dimensional polymer full-network cross-linked structure generated by interfacial polymerization at the interface of amine monomer molecules and organic solvents, and has extremely strong stability in water and organic solvents.
[0009] Preferably, the polyamide selective separation layer structure includes one or more of polyimide (-CO-N-CO-) and polyamide (-NH-CO-) structures;
[0010] Specifically, the porous ultrafiltration substrate is selected from an organic polymer substrate, an inorganic substrate or an organic / inorganic hybrid ultrafiltration substrate, and has an average pore size of 0.001-100 μm.
[0011] Specifically, the porous base membrane may be in the form of a flat plate, a tube or a hollow fiber.
[0012] In a second aspect, the present invention provides a method for preparing the composite film, comprising:
[0013] Step a, washing the surface of the porous ultrafiltration substrate with organic and inorganic solvents for multiple times to remove organic matter and inorganic dust on the surface, rinsing the surface solvent with deionized water and storing it in deionized water for later use;
[0014] Step b, placing a certain amount of amine monomer in a solid volatilization device; wiping the water droplets on the surface of the porous ultrafiltration substrate in step a clean, and placing it above the volatilization device, adjusting the temperature of the volatilization device, and maintaining it for a certain time, so that the amine molecules volatilize and adsorb on the surface of the porous ultrafiltration substrate;
[0015] Step c, dissolving a certain amount of acyl chloride monomer in an organic solvent to prepare an acyl chloride solution, and stirring until a transparent and uniform solution is obtained; the porous ultrafiltration substrate with the amine monomer adsorbed on the surface in step b is immediately immersed in the acyl chloride solution, and after a period of reaction, it is immersed in an organic solvent to remove the unreacted acyl chloride monomer, so as to obtain a narrow pore magnesium-lithium separation nanofiltration membrane.
[0016] Specifically, the organic and inorganic solvents described in step a are selected from at least one of methanol, ethanol, benzene, toluene, ether and deionized water.
[0017] Specifically, the amino monomer described in step b is preferably: one or more of o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, piperazine, bis(4-aminophenyl) ether, 4,4'-diaminodiphenyl sulfone, 1,4-bis(4-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, and tetrakis(4-aminophenyl)-methane; the temperature of the volatilization device is 25-100° C.; and the holding time is 1-60 min.
[0018] Specifically, the acyl chloride monomer in step c is selected from one or more of terephthaloyl chloride, trimesoyl chloride, biphenyl tetrachloride, biphenyl hexachloride, and 1,5-naphthalene disulfonyl chloride; the concentration of the acyl chloride monomer is 0.1-5wt%; the stirring time of the acyl chloride solution is 0.5-6h; and the reaction time is 5-300s.
[0019] Specifically, the organic solvent described in step c is selected from at least one of n-hexane, benzene and toluene.
[0020] The nanofiltration membrane obtained by the present invention is used for seawater desalination, lithium extraction from salt lakes, precision separation, and wastewater treatment, such as magnesium-lithium separation, rare earth concentration, etc.
[0021] The technical solution provided by the present invention has the following beneficial effects: the present invention in situ grows a selective separation layer of a two-dimensional mesh structure on a porous ultrafiltration substrate. The formed separation layer has a uniform narrow pore size distribution, and can achieve precise separation of magnesium ions and lithium ions while meeting the nanofiltration performance. In addition, the method of the present invention is simple and easy to implement, and the two-dimensional mesh separation layer can be uniformly grown on the surface of a variety of substrates. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 . Transmission electron microscopy images of the surface (1-1) and cross-section (1-2) of the polyamide nanofiltration membrane prepared in Example 1 of the present invention.
[0023] Figure 2 .Surface pore size distribution diagram of the polyamide nanofiltration membrane prepared in Example 1 of the present invention.
[0024] Figure 3. Transmission electron microscopy images of the surface (2-1) and cross-section (2-2) of the polyamide nanofiltration membrane prepared in Example 2 of the present invention.
[0025] Figure 4 .Radio electron microscopy images of the surface of the polyamide filter membrane (3-1) and the cross-sectional surface (3-2) prepared in Comparative Example 1 of the present invention.
[0026] Figure 5 .Surface pore size distribution diagram of the polyamide nanofiltration membrane prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0027] To make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be further described in detail below in conjunction with the accompanying drawings, but the present invention is not limited to the following embodiments.
[0028] In a first aspect, an embodiment of the present invention provides a narrow pore size magnesium-lithium separation nanofiltration membrane, comprising a porous ultrafiltration substrate and a selective separation layer of a polyamide material in-situ grown on the surface of the porous substrate;
[0029] The polyamide material is a two-dimensional polymer full-network cross-linked structure generated by interfacial polymerization at the interface of amine monomer molecules and organic solvents, and has extremely strong stability in water and organic solvents.
[0030] Preferably, the polyamide selective separation layer structure comprises one or more of polyamide (-NH-CO-) and polyimide (-N-CO-) structures; usually, primary amines form polyamide (-NH-CO-) and secondary amines form polyimide (-N-CO-).
[0031] Specifically, preferably, the thickness of the selective separation layer of the polyamide material is 2 nm to 200 nm.
[0032] Specifically, as a preference, the porous ultrafiltration substrate is selected from an organic polymer substrate, an inorganic substrate or an organic / inorganic hybrid ultrafiltration substrate, and has an average pore size of 0.001-100 μm;
[0033] In a second aspect, an embodiment of the present invention provides a method for preparing the composite film, comprising:
[0034] Step 101, washing the surface of the porous ultrafiltration substrate with organic and inorganic solvents for multiple times to remove organic matter and inorganic dust on the surface, rinsing the surface solvent with deionized water and storing it in deionized water for later use;
[0035] Step 102, placing a certain amount of amine monomer in a solid volatilization device; wiping the water droplets on the surface of the porous ultrafiltration substrate in step 101, and placing it above the volatilization device, adjusting the temperature of the volatilization device, and maintaining it for a certain period of time, so that the amine molecules volatilize and adsorb on the surface of the porous ultrafiltration substrate.
[0036] Step 103, dissolving a certain amount of acyl chloride monomer in an organic solvent to prepare an acyl chloride solution, and stirring until a transparent and uniform solution is obtained; the porous ultrafiltration substrate with the amine monomer adsorbed on the surface in step 102 is immediately immersed in the acyl chloride solution, and after a period of reaction, immersed in an organic solvent to remove unreacted acyl chloride monomer, so as to obtain a narrow pore magnesium-lithium separation nanofiltration membrane.
[0037] Specifically, the organic and inorganic solvents described in step 101 are selected from at least one of methanol, ethanol, benzene, toluene, ether, and deionized water. The concentration of the organic solvent can be 10wt%, 30wt%, 50wt%, 70wt%, or 90wt%.
[0038] Specifically, the amino monomer described in step 102 is preferably: one or more of o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, piperazine, bis(4-aminophenyl)ether, 4,4'-diaminodiphenyl sulfone, 1,4-bis(4-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, and tetrakis(4-aminophenyl)-methane; the mass of the amino monomer is 0.1-5g, the temperature of the volatilization device is 25-100°C; and the holding time is 1-60min. The mass of the amine monomer can be 0.5g, 1g, 1.5g, 2g, 2.5g, 3g, 3.5g, 4g, 4.5g, 5g; the temperature can be 25℃, 30℃, 35℃, 40℃, 50℃, 60℃, 75℃, 100℃; the holding time can be 5min, 10min, 15min, 20min, 30min, 45min, 60min. In this way, the amine monomer can be sufficiently volatilized so that a layer of defect-free amine molecules is adsorbed on the substrate surface.
[0039] Specifically, the acyl chloride monomer in step 103 is selected from one or more of terephthaloyl chloride, trimesoyl chloride, biphenyl tetrachloride, biphenyl hexachloride, and 1,5-naphthalene disulfonyl chloride; the concentration of the acyl chloride monomer is 0.1-2wv%; the stirring time of the acyl chloride solution is 0.5-6h; and the reaction time is 5-300s. The concentration of the acyl chloride monomer can be 0.2wv%, 0.5%wv%, 1wv%, 2wv%; and the reaction time can be 10s, 30s, 60s, 90s, 120s, 180s, 240s, or 300s. In this way, the amine monomer and the acyl chloride monomer can react completely to form a dense polyamide separation layer.
[0040] Specifically, the organic solvent in step 103 is selected from at least one of n-hexane, benzene and toluene.
[0041] The present invention will be further described below through specific examples.
[0042] In the following specific examples, the operations involved, if the conditions are not specified, are all carried out under conventional conditions or conditions recommended by the manufacturer. The raw materials used, if the manufacturers and specifications are not specified, are all conventional products that can be obtained from the market.
[0043] Example 1
[0044] A polyacrylonitrile (PAN) porous ultrafiltration substrate is used, and the average pore size of the substrate is 50 nm; 30% anhydrous ethanol is selected to wash the surface of the substrate.
[0045] Step a, washing the surface of the polyacrylonitrile porous ultrafiltration substrate with 30% anhydrous ethanol for multiple times to remove organic matter and inorganic dust on the surface, rinsing the surface solvent with deionized water and storing it in deionized water for later use;
[0046] Step b, placing 1 g of piperazine monomer in a solid volatilization device; wiping the water droplets on the surface of the polyacrylonitrile ultrafiltration substrate in step a clean, and placing it above the volatilization device, adjusting the temperature of the volatilization device to 40° C., and maintaining it for 10 minutes, so that the amine molecules volatilize and adsorb on the surface of the porous ultrafiltration substrate.
[0047] Step c, dissolving trimesoyl chloride in n-hexane to prepare a 0.2wv% acyl chloride solution, stirring for 30 minutes to obtain a transparent uniform solution; immediately immersing the polyacrylonitrile ultrafiltration substrate with amine monomer adsorbed on the surface in step b in the acyl chloride solution, reacting for 30 seconds and then immersing it in n-hexane solvent to remove unreacted acyl chloride monomer, thereby obtaining a narrow pore magnesium-lithium separation nanofiltration membrane.
[0048] SEM photos ( Figure 1 ) showed that the surface of the polyamide nanofiltration membrane was dense, without pinholes and defects, and the thickness of the selective separation layer was about 35nm.
[0049] MWCO proves that the surface of polyamide nanofiltration membrane has a narrow pore size distribution, and the pore size is approximately ( Figure 2 ).
[0050] The prepared nanofiltration membrane was placed in a cross-flow nanofiltration evaluation device for performance testing. The test conditions were as follows: (1) the stock solution composition was 1 g / L Na 2 SO 4 water system, (2) the stock solution composition is 1g / L NaCl water system, (3) the stock solution composition is 1g / L MgCl 2water system, (4) the stock solution composition is 1g / L LiCl water system, (5) the stock solution composition is 2g / L MgCl 2 and LiCl mixed water system, where the mass ratio of magnesium to lithium is 30, (6) the stock solution composition is 1g / L GdCl 3 Water system.
[0051] The measured nanofiltration membrane performance is: (1) Na 2 SO 4 The rejection rate of (1) NaCl is 97.32% and the permeate flux is 13.54 LMH / bar. (2) The rejection rate of (2) NaCl is 21.55% and the permeate flux is 20.32 LMH / bar. (3) MgCl 2 The rejection rate of is 93.9% and the permeate flux is 16.41LMH / bar. (4) The rejection rate of LiCl is 20.12% and the permeate flux is 18.83LMH / bar. (5) The selectivity of magnesium and lithium is 78. (6) GdCl 3 The rejection rate is 97.38% and the permeate flux is 14.83LMH / bar.
[0052] Example 2
[0053] A polyacrylonitrile (PAN) porous ultrafiltration substrate is used, and the average pore size of the substrate is 50 nm; 30% anhydrous ethanol is selected to wash the surface of the substrate.
[0054] Step a, washing the surface of the polyacrylonitrile porous ultrafiltration substrate with 30% anhydrous ethanol for multiple times to remove organic matter and inorganic dust on the surface, rinsing the surface solvent with deionized water and storing it in deionized water for later use;
[0055] Step b, placing 1 g of monomer in a solid volatilization device; wiping the water droplets on the surface of the polyacrylonitrile ultrafiltration substrate in step a clean, and placing it above the volatilization device, adjusting the temperature of the volatilization device to 35° C., and maintaining it for 15 minutes, so that the amine molecules volatilize and adsorb on the surface of the porous ultrafiltration substrate.
[0056] Step c, dissolving trimesoyl chloride in n-hexane to prepare a 0.2wv% acyl chloride solution, stirring for 1 hour to obtain a transparent and uniform solution; immediately immersing the polyacrylonitrile ultrafiltration substrate with amine monomer adsorbed on the surface in step b in the acyl chloride solution, reacting for 180 seconds and then immersing in an organic solvent to remove unreacted acyl chloride monomer, thereby obtaining a narrow pore magnesium-lithium separation nanofiltration membrane.
[0057] SEM photos ( Figure 3 ) showed that the surface of the polyamide nanofiltration membrane was dense, without pinholes and defects, and the thickness of the selective separation layer was about 55nm.
[0058] The prepared nanofiltration membrane was placed in a cross-flow nanofiltration evaluation device for performance testing. The test conditions were as follows: (1) the stock solution composition was 1 g / L Na 2 SO 4 water system, (2) the stock solution composition is 1g / L NaCl water system, (3) the stock solution composition is 1g / L MgCl 2 water system, (4) the stock solution composition is 1g / L LiCl water system, (5) the stock solution composition is 2g / L MgCl 2 A mixed water system with LiCl, wherein the mass ratio of magnesium to lithium is 30.
[0059] The measured nanofiltration membrane performance is: (1) Na 2 SO 4 The rejection rate of (1) NaCl is 95.28% and the permeate flux is 15.09 LMH / bar. (2) The rejection rate of (2) NaCl is 20.32% and the permeate flux is 21.90 LMH / bar. (3) MgCl 2 The rejection rate of (4) LiCl is 23.13% and the permeate flux is 21.9 LMH / bar.
[0060] (5) The magnesium-lithium selectivity is 58.
[0061] Example 3
[0062] A polyethersulfone (PES) porous ultrafiltration substrate was used, and the average pore size of the substrate was 50 nm; 30% anhydrous ethanol was selected to wash the surface of the substrate.
[0063] Step a, washing the surface of the polyacrylonitrile porous ultrafiltration substrate with 30% anhydrous ethanol for multiple times to remove organic matter and inorganic dust on the surface, rinsing the surface solvent with deionized water and storing it in deionized water for later use;
[0064] Step b, placing 1 g of monomer in a solid volatilization device; wiping the water droplets on the surface of the polyacrylonitrile ultrafiltration substrate of step a clean, and placing it above the volatilization device, adjusting the temperature of the volatilization device to 45° C., and maintaining it for 10 minutes, so that the amine molecules volatilize and adsorb on the surface of the porous ultrafiltration substrate.
[0065] Step c, dissolving trimesoyl chloride in n-hexane to prepare a 0.2wv% acyl chloride solution, stirring for 1 hour to obtain a transparent and uniform solution; immediately immersing the polyacrylonitrile ultrafiltration substrate with the amine monomer adsorbed on the surface in step b in the acyl chloride solution, reacting for 30 seconds and then immersing in an organic solvent to remove unreacted acyl chloride monomers, thereby obtaining a narrow pore magnesium-lithium separation nanofiltration membrane.
[0066] The prepared nanofiltration membrane was placed in a cross-flow nanofiltration evaluation device for performance testing. The test conditions were as follows: (1) the stock solution composition was 1 g / L Na 2 SO 4 water system, (2) the stock solution composition is 1g / L NaCl water system, (3) the stock solution composition is 1g / L MgCl 2 water system, (4) the stock solution composition is 1g / L LiCl water system, (5) the stock solution composition is 2g / L MgCl 2 and LiCl mixed water system, in which the mass ratio of magnesium to lithium is 30.
[0067] The measured nanofiltration membrane performance is: (1) Na 2 SO 4 The rejection rate of (1) NaCl is 96.28, and the permeate flux is 14.61 LMH / bar. (2) The rejection rate of NaCl is 21.87%, and the permeate flux is 21.45 LMH / bar. (3) MgCl 2 The rejection rate of 90.18% and the permeate flux of 16.42LMH / bar. (4) The rejection rate of LiCl is 19.48% and the permeate flux is 22.19LMH / bar. (5) The selectivity of magnesium and lithium is 62.
[0068] Comparative Example 1
[0069] This comparative example adopts the traditional liquid-liquid interfacial polymerization method to prepare the polyamide nanofiltration membrane.
[0070] A polyacrylonitrile (PAN) porous ultrafiltration substrate is used, and the average pore size of the substrate is 50 nm; 30% anhydrous ethanol is selected to wash the surface of the substrate.
[0071] Step a, washing the surface of the polyacrylonitrile porous ultrafiltration substrate with 30% anhydrous ethanol for multiple times to remove organic matter and inorganic dust on the surface, rinsing the surface solvent with deionized water and storing it in deionized water for later use;
[0072] Step b, dissolving 1 g of piperazine in 100 mL of deionized water, stirring for 30 min to obtain a transparent uniform solution; dissolving 0.2 g of trimesoyl chloride monomer in 100 mL of n-hexane to prepare a 0.2 wv% acyl chloride solution, stirring for 30 min to obtain a transparent uniform solution.
[0073] Step c, wipe off the water droplets on the surface of the porous base membrane in step a, and place it in a piperazine aqueous solution for 30 seconds to make the membrane surface and pores rich in amine molecule solution. After taking it out, wipe off the water droplets on the surface of the membrane first, then immerse it in a benzyl chloride solution, react for 30 seconds, and then immerse it in n-hexane solvent for 30 seconds to remove unreacted acyl chloride monomers, and then a traditional polyamide nanofiltration membrane can be obtained.
[0074] SEM photos ( Figure 4-1 ) showed that the surface of the polyamide nanofiltration membrane was dense, without pinholes and defects, and the thickness of the selective separation layer was about 62nm.
[0075] MWCO proves that the surface of polyamide nanofiltration membrane has a wide pore size distribution, and the pore size is approximately ( Figure 5 ).
[0076] The prepared nanofiltration membrane was placed in a cross-flow nanofiltration evaluation device for performance testing. The test conditions were as follows: (1) the stock solution composition was 1 g / L Na 2 SO 4 water system, (2) the stock solution composition is 1g / L NaCl water system, (3) the stock solution composition is 1g / L MgCl 2 water system, (4) the stock solution composition is 1g / L LiCl water system, (5) the stock solution composition is 2g / L MgCl 2 A mixed water system with LiCl, wherein the mass ratio of magnesium to lithium is 30.
[0077] The measured nanofiltration membrane performance is: (1) Na 2 SO 4 The rejection rate of (1) NaCl is 96.59% and the permeate flux is 14.88 LMH / bar. (2) The rejection rate of (2) NaCl is 21% and the permeate flux is 23.7 LMH / bar. (3) MgCl 2 The rejection rate of is 77.5% and the permeate flux is 22.02LMH / bar. (4) The rejection rate of LiCl is 20.32% and the permeate flux is 23.95LMH / bar. (5) The selectivity of magnesium and lithium is 3.2. (6) GdCl 3 The rejection rate is 92.76% and the permeate flux is 16.92LMH / bar.
[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a narrow pore size magnesium-lithium separation nanofiltration membrane, comprising a porous ultrafiltration substrate and a polyamide selective separation layer in situ grown on the surface of the porous ultrafiltration substrate, characterized in that: The polyamide selective separation layer is a two-dimensional polymer full-network cross-linked structure generated by interfacial polymerization at the amine monomer molecule-organic solvent interface; The polyamide selective separation layer structure includes one or more of polyimide (-N-CO-) and polyamide (-NH-CO-) structures; The preparation method comprises the following steps: Step a, washing the surface of the porous ultrafiltration substrate with organic and inorganic solvents for multiple times to remove organic matter and inorganic dust on the surface, rinsing the surface solvent with deionized water and storing it in deionized water for later use; Step b, placing a certain amount of amine monomer in a solid volatilization device; wiping the water droplets on the surface of the porous ultrafiltration substrate in step a clean, and placing it above the volatilization device, adjusting the temperature of the volatilization device, and maintaining it for a certain time, so that the amine molecules volatilize and adsorb on the surface of the porous ultrafiltration substrate; Step c, dissolving a certain amount of acyl chloride monomer in an organic solvent to prepare an acyl chloride solution, and stirring until a transparent and uniform solution is obtained; immediately immersing the porous ultrafiltration substrate with the amine monomer adsorbed on the surface in step b in the acyl chloride monomer solution, and after a period of reaction, immersing it in an organic solvent to remove unreacted acyl chloride monomer, thereby obtaining a magnesium-lithium separation nanofiltration membrane with a narrow pore size; The amino monomer in step b is selected from one or more of o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, piperazine, bis(4-aminophenyl)ether, 4,4'-diaminodiphenyl sulfone, 1,4-bis(4-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, and tetrakis(4-aminophenyl)-methane; the temperature of the volatilization device is 25-100°C; the holding time is 1-60min; The acyl chloride monomer in step c is selected from one or more of terephthaloyl chloride, trimesoyl chloride, biphenyl tetrachloride, biphenyl hexachloride, and 1,5-naphthalene disulfonyl chloride; the concentration of the acyl chloride monomer is 0.1-5 wt %; the stirring time of the acyl chloride solution is 0.5-6 h; and the reaction time is 5-300 s.
2. The method for preparing a narrow pore size magnesium-lithium separation nanofiltration membrane according to claim 1, characterized in that: The thickness of the polyamide selective separation layer is 2 nm to 200 nm.
3. The method for preparing a narrow pore size magnesium-lithium separation nanofiltration membrane according to claim 1, characterized in that: The porous ultrafiltration substrate is selected from an organic polymer substrate, an inorganic substrate or an organic / inorganic hybrid ultrafiltration substrate, and has an average pore size of 0.001-100 μm.
4. The method for preparing a narrow pore size magnesium-lithium separation nanofiltration membrane according to claim 1, characterized in that: The porous ultrafiltration substrate is in the shape of a flat plate, a tube or a hollow fiber.
5. The method for preparing a narrow pore size magnesium-lithium separation nanofiltration membrane according to claim 1, characterized in that: The organic and inorganic solvents described in step a are selected from at least one of methanol, ethanol, benzene, toluene, ether, and deionized water; The organic solvent described in step c is selected from at least one of n-hexane, benzene and toluene.
6. The method for preparing a narrow pore size magnesium-lithium separation nanofiltration membrane according to claim 1, characterized in that: The temperature of the volatilization device in step c is 25-100° C.; the volatilization device adopts a water bath, oil bath, sand bath or oven heating equipment.
7. A narrow pore magnesium-lithium separation nanofiltration membrane prepared according to the method described in any one of claims 1 to 6.
8. Application of a narrow pore magnesium-lithium separation nanofiltration membrane prepared according to the method described in any one of claims 1 to 6 for magnesium-lithium separation.
Citation Information
Patent Citations
Nanofiltration membrane, preparation method and application thereof
CN111659270A
Composite nanofiltration membrane with ultrahigh lithium-magnesium selectivity as well as preparation method and application of composite nanofiltration membrane
CN114432907A
Thin-film composite nanofiltration membrane as well as preparation method and application thereof
CN114682103A
Preparation Method of Polyamide Thin Film Composite Reverse Osmosis Membrane and Polyamide Thin Film Composite Reverse Osmosis Membrane Prepared Therefrom
US20080234462A1
Supramolecular composite nano-filtration membrane and preparation method therefor and use thereof
WO2018120476A1
